The System of the Educational Process of Pupils with Disabilities in Ukraine - Stárek, Lukáš (International Journal of Membrane Science and Technology, 2023)
This expert text brings thought and reflection to the system of special pedagogy in Ukraine. We hear about this country in the context of a war conflict, and other equally important areas are unknown to us. At the present stage, new perspectives have shown up in the system of correctional education related to the rethinking of the attitude to the organisation of education and upbringing of children with special needs. Authorities, pedagogues, and ordinary citizens seek to come closer to understanding the difficulties these individuals face; actively discuss the benefits of special or integrated education; try to create certain conditions for their life (ramps, sign language translation, etc.); implement foreign experience. The practice of European countries, the United States, and Canada shows that children with special needs can be educated not only in special, separate from general education institutions, but also in usual schools on the model of integrated or inclusive education, which provides quality educational services to children regardless level of their development. The introduction of modern models of education, upbringing, and rehabilitation of children with psychophysical development requires not only a special organisation of the material environment, but also training of psychological and pedagogical staff of secondary schools, as the effectiveness of integrated and inclusive education depends on proper psychological and pedagogical support of these children. Non-governmental organisations, including organisations of parents of children with special educational needs, play a significant role in implementing such changes in Ukrainian society.